2008
DOI: 10.1161/circimaging.108.768911
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Root Measurement by Cardiovascular Magnetic Resonance

Abstract: Background-Cardiovascular magnetic resonance is widely used for aortic root visualization and measurement, but methods still need to be standardized. Our aim was to identify appropriate planes of acquisition and lines of measurement and record corresponding normal values. Methods and Results-We studied 120 healthy volunteers, 10 of each gender in each decile between 20 and 80 years, by using a 1.5-T cardiovascular magnetic resonance system. Steady-state free precession cine acquisitions aligned with the left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(59 citation statements)
references
References 15 publications
2
57
0
Order By: Relevance
“…Root dimensions may be measured from cusp to cusp or from cusp to commissure, producing 3 diameters that are subsequently averaged. 23 The optimal definition for aortic root dilatation remains controversial. Normal aortic size is determined by age, sex, body size, location of the measurement, and robustness of the imaging modality.…”
Section: Discussionmentioning
confidence: 99%
“…Root dimensions may be measured from cusp to cusp or from cusp to commissure, producing 3 diameters that are subsequently averaged. 23 The optimal definition for aortic root dilatation remains controversial. Normal aortic size is determined by age, sex, body size, location of the measurement, and robustness of the imaging modality.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,18 However, with this imaging modality, the aortic valve annulus is assumed to be circular, although it has been demonstrated that this structure has an ellipsoid shape. 5,7 In this regard, Babaliaros et al 19 studied 23 patients with severe AS and demonstrated that transthoracic or transesophageal echocardiography underestimated the size of the aortic valve annulus by .1.7 and .1.2 mm, respectively, when compared with the measurement performed intraoperatively with surgical sizers. 19 The authors addressed the ellipsoid shape of the aortic valve annulus, and not an inaccuracy of this two-dimensional imaging technique, as the main cause of these differences.…”
Section: Discussionmentioning
confidence: 99%
“…13 Aortic measurements were obtained at the following 5 levels (Figure 1): neoaortic root, mid-AAo, distal transverse arch, isthmus, and descending aorta at the level of the diaphragm. Each aortic segment was reformatted in a double oblique plane, and 2 orthogonal measurements were recorded at each level as described by Kaiser et al 14 The aortic root was measured from sinus-to-commissure in one dimension (labeled as anteroposterior [AP]) and cusp-to-cusp in the other (labeled as lateral dimension) according to the method of Burman et al 15 The pulmonary arteries were similarly measured as described by Knobel et al 16 Body surface area (BSA) at the time of CMR was calculated from the patient height and weight using the method of Haycock et al 17 Volumetric measurements were adjusted to BSA 1.3 , and linear measurements were indexed to BSA 0.5 . 18-20 z scores were calculated from published normal values.…”
Section: Cmr Measurementsmentioning
confidence: 99%